Communication between parents and neonatal healthcare professionals using pictorial support when language barriers exist – parents' experiences. Issue 1 (31st December 2022) - Gotting, Eva-Karin; Ferm, Ulrika; Wigert, Helena
ABSTRACT: Purpose: Families arriving in Sweden after being forced to flee their home need health care. Communication is a key component to establishing good care relations and becomes difficult when there are language barriers between families and healthcare professionals. In the context of neonatal care, communication is carried out with parents. The aim of the study was to describe parents' experiences of communication with neonatal healthcare professionals and using pictorial support when language barriers exist. Method: The study takes a qualitative approach based on seventeen interviews with parents who had experienced neonatal ward. Qualitative content analysis was used. Results: The parents needed to communicate through supports, which caused distress and misunderstanding. The relationship between parents and the healthcare professionals affected the communication. Pictorial support was used to different degrees. Four categories were identified from the data analysis: Communicating through supports, Facing barriers in communication, Facing external influences and The need for a good healthcare relationship. Conclusion: The present study is the first to describe parents' experience with using the pictorial support developed in the project KomHIT Refugee and therefore fulfils the function of being a first evaluation of the pictures from parents' perspective.